Migration in the Context of Globalization: Key Trends and Dynamics - Delovarova, L; Kukeyeva, F (Farabi Journal of Social Sciences, 2016)
Migration is a permanent phenomenon of the modern international relations. Globalization has led to new migration trends that have changed the traditional understanding of migration. Globalization of migration, acceleration of migration, feminization the increasing role of labor migration, differentiation of migration and unprecedented growth of illegal migration are the new migration trends which cause serious changes in the social, political, economic and cultural fields of regions and countries worldwide. The new migration trends require some new and more effective approaches to manage the issues caused by the trends in order to strength its positive effects and minimize its negative influence on the integration and processes in the field of migration